1991
DOI: 10.1111/j.1464-410x.1991.tb15161.x
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Factors in the Conservative Treatment of Ureteric Stones

Abstract: A prospective study was made of 125 ureteric stones in order to detect factors which would predict the successful outcome of conservative treatment. The factors studied were the duration of pain prior to presentation, pyuria, haematuria, surface regularity of the stone and the degree of obstruction as seen radiologically. In stones less than or equal to 10 mm in size, conservative treatment was successful when the duration of pain was less than 30 days (39/45), when there was no significant pyuria (53/82), whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
39
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(42 citation statements)
references
References 6 publications
3
39
0
Order By: Relevance
“…The important question of predicting intervention in renal colic has, for decades, only been addressed through retrospective studies showing that persistence of pain, size of calculus, location along the ureter, impaired renal function, obstruction and signs of infection are important factors influencing intervention. 8,15,[19][20][21][22][23] Our predictive variables for intervention are remarkably similar to other studies 8,12,15,[23][24][25] and demonstrate that our sample of renal colic patients is comparable to other populations described in the literature. 14,[26][27][28] Although not all patients had an intervention or were enrolled in the study, we Not enrolled in study n = 81…”
Section: Discussionsupporting
confidence: 76%
“…The important question of predicting intervention in renal colic has, for decades, only been addressed through retrospective studies showing that persistence of pain, size of calculus, location along the ureter, impaired renal function, obstruction and signs of infection are important factors influencing intervention. 8,15,[19][20][21][22][23] Our predictive variables for intervention are remarkably similar to other studies 8,12,15,[23][24][25] and demonstrate that our sample of renal colic patients is comparable to other populations described in the literature. 14,[26][27][28] Although not all patients had an intervention or were enrolled in the study, we Not enrolled in study n = 81…”
Section: Discussionsupporting
confidence: 76%
“…Resim et al did not identify a significant difference in distal stone passage rates between the tamsulosin and control groups. Similar expulsion rates were seen when patients with 6 mm stones were evaluated separately from those with stones larger than 6 mm [20]. In that trial, the average time to stone passage was not reported, the similar passage rates may be related to the longer treatment duration of 42 days, approaching the time when stone passage would spontaneously occur.…”
Section: Discussionsupporting
confidence: 51%
“…Studies have shown stone passage rates from 71-98% for distal ureteral stones less than 5 mm and from 25-53% for those between 5 and 10 mm. 16 Although two thirds of the ureteral stones passed spontaneously within 4 weeks after the onset of symptoms, the rate of complications such as sepsis was directly related to the symptom duration, reaching 20% when the symptom lasted for more than 4 weeks. 17 The presence of alpha-and beta-adrenergic receptors in the human ureter was first described in 1970.…”
Section: Discussionmentioning
confidence: 99%